Inkjet printing for biosensor fabrication: combining chemistry and technology for advanced manufacturing. Issue 12 (21st June 2015) - Li, Jia; Rossignol, Fabrice; Macdonald, Joanne
<x xml:space="preserve">Abstract</x> Inkjet printing is emerging at the forefront of biosensor fabrication technologies.